Functional Applications of Polymer Electrolytes in High‐Energy‐Density Lithium Batteries. Issue 8 (12th January 2022) - Wang, Yuanyuan; Zhai, Fangfang; Zhou, Qian; Lv, Zhaolin; Jian, Li; Han, Pengxian; Zhou, Xinhong; Cui, Guanglei
Abstract: Polymer electrolytes have attracted great interest in advanced lithium batteries. Recently, it has been found that there are many functional applications of polymer electrolytes in lithium batteries, which are very important for the development of high‐energy‐density lithium batteries. In this review, the functional applications of polymer electrolytes are reviewed in terms of protecting lithium metal anode, coating for high‐voltage cathodes, and improving the safety of batteries. Finally, the remaining challenges and future perspectives of polymer electrolytes in these functional applications are presented. This review aims to provide a comprehensive understanding of polymer electrolytes and promotes their functional application in high‐energy‐density lithium batteries. Abstract : There functional applications of polymer electrolytes are very important for the development of high‐energy‐density lithium batteries. This review has summarized the functional applications of polymer electrolytes in terms of protecting lithium metal anode, coating for high‐voltage cathodes, and improving the safety of batteries. Meanwhile, the remaining challenges and future perspectives of polymer electrolytes in these functional applications are presented.